Wnt Signaling Pathway Related Genes In Hepatocellular Carcinoma - Ban, Kechen (2002)
Hepatocellular carcinoma (HCC) is an extremely difficult disease to manage and one of the ten most common cancers in Malaysia. However, the molecular mechanisms that contribute to tumour progression in hepatocarcinogenesis remain unknown. In recent years, the evidence that the Wnt signaling pathway may play a crucial role in the hepatocarcinogenesis represents a major breakthrough. Despite efforts made in this area of research, the relationship between the related genes of Wnt signaling pathway is still far from comprehensive. By employing immunohistochemistry and DNA sequencing, some related proteins and genes of the Wnt signaling pathway were investigated in 23 paired HCC and adjacent liver specimens from a tertiary referral centre in Malaysia.